Bermain Sambil Belajar: Upaya Peningkatan Calistung pada Anak Yatim dan Putus Sekolah di Desa Ampung Julu - Farid, Ahmad Salman (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
This activity was carried out in response to the challenge of low literacy rates among orphaned and school drop-out children in the village of Ampung Julu, Batang Natal District, Mandailing Natal Regency. The evaluation results indicate a significant improvement in the reading, writing, and arithmetic skills of children, confirming that educational games can be an effective method in shaping academic skills. The program also instilled high intrinsic motivation among the children, perceiving learning as an enjoyable experience. In addition to the positive impact on academic aspects, educational games also foster social and emotional skills in children, creating a crucial foundation for holistic personal development. The success of the program relies not only on the contributions of the students but also actively involves the participation of the local community, including parents and village authorities. This close collaboration creates sustainable support and enhances the positive impact of the program. These outcomes not only bring about changes in the education of children but also alter the community's perception of the significance of education as a tool for creating positive changes in their lives. The success of the "Learn Through Play" program serves as inspiration for the development of similar initiatives in various regions facing similar educational challenges. This contribution adds value to the conceptualization and planning of innovative education ideas and models that can be adopted on a broader scale. Thus, this community engagement does not only create tangible changes at the local level but also provides a valuable contribution to the thinking and planning of innovative education at a broader level.